Seed Quality Deterioration of Cotton During Storage - Prasad, Rajendra (Asian Journal of Chemistry, 2010)
Cotton seeds of genetically different varieties of Gossypium hirsutum and Gossypium arboreum were collected and stored for two years under ambient conditions. At the time of storage the' percentage of seed oil, starch, nitrogen, fatty acids and amino acids (μg g-1) were determined. At the end of the storage period nitrogen content, starch and oil percentage decreased while the free fatty acids and amino acids increased. The nitrogen contents and consequently the crude protein content decreased because of its hydrolysis, and hence the amino acids showed an increase in its contents. Free fatty acids increased due to the action of lipases on fats and due to this oil content decreased during the study. The decrease in starch was perhaps due to the activity of hydrolytic enzymes of starch with increasing moisture and temperature as well as storage period.